2021
DOI: 10.1002/dta.3104
|View full text |Cite
|
Sign up to set email alerts
|

Determination of buprenorphine, norbuprenorphine, naloxone, and their glucuronides in urine by liquid chromatography–tandem mass spectrometry

Abstract: A liquid chromatography-tandem mass spectrometry method for the simultaneous quantification of buprenorphine (BUP), norbuprenorphine (NBUP), naloxone (NAL), and their glucuronide conjugates BUP-G, NBUP-G, and NAL-G in urine samples was developed. The method, omitting a hydrolysis step, involved non-polar solid-phase extraction, liquid chromatography on a C18 column, electrospray positive ionization, and mass analysis by multiple reaction monitoring. Quantification was based on the corresponding deuterium-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 58 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…In our previous methodological study, we found the following median (maximum) concen- (2310 μg/L). 25 The median NBUPG/BUPG and NBUPtot/BUPtot concentration ratios were 1.8 and 2.5, respectively. These results are consistent with those of the relatively few other published studies on free and total drug concentrations in opioid-dependent patients in OAT.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In our previous methodological study, we found the following median (maximum) concen- (2310 μg/L). 25 The median NBUPG/BUPG and NBUPtot/BUPtot concentration ratios were 1.8 and 2.5, respectively. These results are consistent with those of the relatively few other published studies on free and total drug concentrations in opioid-dependent patients in OAT.…”
Section: Resultsmentioning
confidence: 89%
“…The LC-MS/MS method has been previously described. 25 The method involved nonpolar solid-phase extraction, separation on a C18 column, electrospray positive ionization, and mass analysis by triple quadrupole MS/MS, using multiple reaction monitoring. Quantification was based on the corresponding deuterium-labelled internal standards for each of the six analytes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations